5(x+3)+x=4(x+5)+3

Simple and best practice solution for 5(x+3)+x=4(x+5)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)+x=4(x+5)+3 equation:


Simplifying
5(x + 3) + x = 4(x + 5) + 3

Reorder the terms:
5(3 + x) + x = 4(x + 5) + 3
(3 * 5 + x * 5) + x = 4(x + 5) + 3
(15 + 5x) + x = 4(x + 5) + 3

Combine like terms: 5x + x = 6x
15 + 6x = 4(x + 5) + 3

Reorder the terms:
15 + 6x = 4(5 + x) + 3
15 + 6x = (5 * 4 + x * 4) + 3
15 + 6x = (20 + 4x) + 3

Reorder the terms:
15 + 6x = 20 + 3 + 4x

Combine like terms: 20 + 3 = 23
15 + 6x = 23 + 4x

Solving
15 + 6x = 23 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
15 + 6x + -4x = 23 + 4x + -4x

Combine like terms: 6x + -4x = 2x
15 + 2x = 23 + 4x + -4x

Combine like terms: 4x + -4x = 0
15 + 2x = 23 + 0
15 + 2x = 23

Add '-15' to each side of the equation.
15 + -15 + 2x = 23 + -15

Combine like terms: 15 + -15 = 0
0 + 2x = 23 + -15
2x = 23 + -15

Combine like terms: 23 + -15 = 8
2x = 8

Divide each side by '2'.
x = 4

Simplifying
x = 4

See similar equations:

| 2x+80-4x=50 | | x(x/3)=12 | | x(x/3) | | x*x/3 | | 9x+2(60)=7x+7(60) | | c=120+.65y | | (2a-3)(4a^2+6a+9)=0 | | 2y+5y(2-y)=3-5y | | x(3x)=8 | | x^2-6x+y=0 | | x^3-4x^2+5x+2=0 | | cos(4*x-(pi))=-0.5 | | -2-3x=4x | | 2x^2+mx-3=0 | | 3X-18=-4 | | 13-6(x-16)=-33 | | 5+(-4x-26)=8 | | 3x^2+4=130 | | 32x-14x=10 | | 22x+35=12x+8 | | 9-5(x-6)=-10 | | 9-3(x-2)=-10 | | (3x-1)(3x+1)=-20 | | 30+1=303129 | | 3X=0.08(3) | | -4+15=17 | | 4-3(x-2)=-10 | | 15x-14=40 | | 2x+2y=142 | | 12b+3=8 | | 4-y/3=-3 | | 1x-40=15 |

Equations solver categories